Stardust and statistics: Situated language and literacy in Pokémon Go guides - Tran, Kelly M. (L1-Educational Studies in Language and Literature, 2022)
The ability to understand language-in-use is essential to language and literacy learning. This article focuses on players' acquisition of specialist language and Discourses (Gee, 2014) among players of the mobile augmented reality game Pokémon GO. Specifically, I explore player-written guides by self-identified researchers of the game. These researchers enact scientific Discourses to explain gameplay elements. Using parent interviews and excerpts from the player-written guides, I analyze these game guides' highly specialized and complex language as forms of situated language in-use. I conclude with a discussion of implications based on these findings for L1 in educational settings.